Treatment of Femoral Neck Fractures with Arthroplasty Method and Our Results, 6 Years Follow-Up, - Kılıç, B., Yücel, A. S., Zekioğlu, A., (My University, 2014)
Background: While femoral neck fractures occur in elderly patients as a result of lowenergy traumas, they occur in young patients as a result of high-energy traumas. Clinical findings indicate that it generally occurs in female and elderly patients who are not mobilized and patients with comorbidity, hip pain and fractured leg in external rotation. These fractures are associated with avascular necrosis and nonunion with high incidence. Early diagnosis is of great importance in order to prevent the complications. Methods: Various treatment methods are available for femoral neck fractures. Choosing the appropriate treatment in femoral neck fractures treatment is very significant for keeping potential mortality and morbidity at minimum level. Generally surgery is the treatment performed. Fixation is the prioritized treatment in young patients. Arthroplasty is preferred method in elderly patients. Conclusion: In our study, we shared 6-years follow-up results of the cemented partial prosthesis that we applied in 57 patients with femoral neck fracture (the mean age is 73,8). All of the patients were enabled to return to their normal lives with the surgery performed at an early period after fracture and with early mobilization. No serious complication arose except for acetabular cartilage erosion that we faced in the long-term and temporary complications in the early post-operative period (injury problems, sore throat and chest pain etc.). In elderly patients, cemented partial prosthesis use is safe and effective.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Neck fracture; arthroplasty; femur